FEATURES OF USE INTERACTIVE TASKS IN MODERN MEANS OF COMPUTER-BASED TRAINING - Victoria V. Bova; Elmar V. Kuliev; Anton A. Novikov (Открытое образование (Москва), 2016)
The article considers the problem of automated generation of interactive activities for learning software. This problem is relevant, since at the present stage of development of computer-based training systems can be traced need to build a tool that allows to implement various types of test and the training tasks on the basis of technologies of interactivity. We propose a tool to create dynamic tasks, enhance student’s interactivity with the system.